Impact of Stock Market Liquidity on Dividend Policy of Nepalese Commercial Banks - Pokhrel, Sandesh; Khadka, Sewak; Acharya, Shrutee; Thapa, Smita; Thapa, Subha (Nepalese Journal of Economics, 2024)
This study examines the impact of stock market liquidity on dividend policy of Nepalese commercial banks. Dividend payout ratio and dividend yield are selected as the dependent variables. The selected independent variables are capitalization, non-performing loan, profitability, liquidity, firm size and lagged market price. The study is based on secondary data of 16 commercial banks with 112 observations for the study period from 2015/16 to 2021/22. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, publications and websites of Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of stock market liquidity on dividend policy of Nepalese commercial banks. The study showed that liquidity has a positive impact on dividend payout ratio and dividend yield. It means that increase in liquidity leads to increase in dividend payout ratio and dividend yield. Furthermore, profitability has a positive impact on dividend payout ratio and dividend yield. It indicates that increase in profitability leads to increase in dividend payout ratio and dividend yield. Likewise, firm size has positive impact on dividend payout ratio and dividend yield. It means that larger the firm size, higher would be the dividend payout ratio and dividend yield. Similarly, lagged market price has a positive impact on dividend payout ratio. It indicates that increase in lagged market price leads to increase in dividend payout ratio. Further, market capitalization has a positive impact on dividend payout ratio. It means higher the market capitalization, higher would be the dividend payout ratio. Likewise, non performing loan has a negative impact on dividend payout ratio. It indicates that increase in non-performing loan leads to decrease in dividend payout ratio.